PERKEMBANGAN BAHASA SEBAGAI SISTEM KOGNITIF ANAK USIA DINI - Sulastri, Made (Program Studi Pendidikan Luar Sekolah, 2022)
Abstract : Language is a tool to communicate, through language humans can interact and communicate to express the results of their thoughts. With language, people can open their horizons of thinking and develop their horizons. In addition to the view that language skills are influenced by cognitive abilities, they also have an understanding that children's language skills are obtained from stimuli that come from outside the child. A child who gets a stimulus in language that is not in accordance with the characteristics of their stage of development, then the stimulus can make them lose playing time which results in a sense of boredom in the learning process. Seeing the picture of the problems that are happening right now like the environment, namely parents, teachers and the community must understand and it is necessary to do research on language development as a cognitive system for early childhood. Data collection methods are observation, interview and documentation methods. The results showed that each child's language development is closely related to the potential and characteristics of children's cognitive development at an early age. The child's cognitive level can be seen from the child's language behavior, the more proficient the child is in language, the higher the child's cognitive level.Keywords: Language, cognitive, early childhoodÂ Abstrak : Bahasa merupakan alat untuk berkomunikasi, melalui bahasa manusia dapat berinteraksi dan berkomunikasi untuk mengemukakan hasil pemikirannya. Dengan bahasa orang dapat membuka cakrawala berfikir dan mengembangkan wawasannya. Pandangan selain kemampuan berbahasa dipengaruhi oleh kemampuan kognitif, mereka juga memiliki pemahaman bahwa kemampuan bahasa anak didapat dari stimulus-stimulus yang berasal dari luar diri anak. Seorang anak yang mendapatkan stimulus dalam berbahasa yang tidak sesuai dengan karakteristik tahap perkembangan mereka, maka stimulus tersebut dapat membuat mereka kehilangan masa bermain yang berakibat timbulnya rasa kejenuhan pada proses belajar. Melihat gambaran masalah yang terjadi saat ini selayaknya lingkungan yaitu orang tua, guru dan masyarakat harus memahami dan perlu dilakukan penelitian tentang perkembangan Bahasa sebagai system kognitif anak usia dini. Metode pengumpulan data yaitu metode observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa setiap anak perkembangan bahasanya sangat berkaitan erat dengan potensi dan karakteristik perkembangan kognitif anak pada usia dini. Tingkat kognitif anak dapat terlihat dari perilaku berbahasa anak, semakin cakap anak dalam berbahasa maka semakin tinggi pula tingkat kognitif anak.Kata kunci : Bahasa, kognitif, anak usia dini